Why Package Child Care? - Maurice King (Paediatrica Indonesiana, 1975)
The team responsible for developing this project starts by considering in detail exactly what workers in Indonesia’s health centres can usefully do (what interventions they can take) in a particular service area, in this case health centre child care. These interventions are being incorporated into a complete, problem oriented illustrated, basic language text of health centre child care. This text is to be supported by a variety of other components which include three matched sets of multiple choice questions covering its entire field, schedules of assessing the practical performance of procedures, equipment lists, methods of quality control, curricula and teaching aids, as well as guidance on the routine administration of the services provided and their initial introduction into a new area. All these components fit together to form a health core package which is defined as "an integrated set of components for the improvement of health care in a defined service area and under specific socio-economic conditions". The hypothesis behind the concept is that the combined effect of the components is more than merely additive.